2007
DOI: 10.1111/j.1440-1673.2007.01873.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre quality assurance of intensity‐modulated radiation therapy plans: A precursor to clinical trials

Abstract: A multicentre planning study comparing intensity-modulated radiation therapy (IMRT) plans for the treatment of a head and neck cancer has been carried out. Three Australian radiotherapy centres, each with a different planning system, were supplied a fully contoured CT dataset and requested to generate an IMRT plan in accordance with the requirements of an IMRT-based radiation therapy oncology group clinical trial. Plan analysis was carried out using software developed specifically for reviewing multicentre cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…In contrast, the CPs were planned by 5 dosimetrists. As mentioned in the ''Introduction,'' there is little doubt that current IMRT planning is associated with a high degree of heterogeneity among institutions and even within the same institutions (3,4). Our method thus provides a consistent and systematic method for generating DVH objectives in IMRT planning.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, the CPs were planned by 5 dosimetrists. As mentioned in the ''Introduction,'' there is little doubt that current IMRT planning is associated with a high degree of heterogeneity among institutions and even within the same institutions (3,4). Our method thus provides a consistent and systematic method for generating DVH objectives in IMRT planning.…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that IMRT plan quality varies among planners by level of experience (3). Even for the same patient, the planning results are often highly heterogeneous (4). Consequently, IMRT plan quality heavily relies on the personal experience of planners and the time they can allocate to a specific plan.…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al[19] has found, using NTCP analysis, that KBP can identify suboptimal plans in large interinstitutional trials even when the trials included rigorous segmentation guidelines and dosimetric OAR constraints. Such variability has been attributed to differences in planning systems, linac capabilities, and institutional experience with the treatment technique[20, 21] but not, to date, individual planner characteristics such as education, certification status, or years of experience[10, 22]. In this study, we were interested in determining whether KBP could identify systematic differences in planning approaches between campuses of a single institution, where again, the same planning system, planning guidelines, and plan evaluation criteria were used.…”
Section: Discussionmentioning
confidence: 99%
“…38. Problems (1) and (2) illustrate the general form of the voxel-based and the organ-based optimization models, respectively,…”
Section: A Voxel-based Optimization Modelmentioning
confidence: 99%
“…Plan quality is subjective and highly dependent on the institution and the planners' skills and experiences. [1][2][3] Automatic treatment planning has been introduced to facilitate this procedure. Two general techniques have been followed in automatic treatment planning.…”
Section: Introductionmentioning
confidence: 99%